Rare Variant of Bartter Syndrome with Sensorineural Deafness - Kumar, Rajesh; Kumar, Pankaj; Kumar, Manoj (Journal of Nepal Paediatric Society, 2016)
Bartter syndrome is an inherited renal tubular disorder characterized by hypokalemia, hypochloremic metabolic alkalosis, hyperreninemia, hyper-prostaglandinism, normal blood pressure, with increased urinary loss of sodium, chloride, potassium, calcium and prostaglandins. There are five known type of Bartter syndrome, out of which type 4 and 5 are very rare. We are presenting here a case of Bartter syndrome with sensorineural hearing loss. J Nepal Paediatr Soc 2015;35(3):293-294.